Identification of Fungi in Marine Algae Kappaphycus alvarezii by Different Maintenance Age - Ariyanto Yusuf; Rully Tuiyo; Mulis Mulis (The NIKe Journal, 2019)
This study aims to determine the type of fungus and calculate the range of fungal colonies on sea algae Kappaphycus alvarezii by maintenance at different ages of 25 days, 35 days and 45 days. Samples taken from the District Anggrek, North Gorontalo District, Province Gorontalo. Method of data processing is descriptive and presentation of data in a frequency distribution table. Methods of testing done by the identification of marine algae samples in the laboratory of Fish Quarantine Station Class I Djalaluddin Gorontalo. The results showed that the fungus identified in the Sea Algae Kappaphycus alvarezii, are Rizhopus sp, Aureobasidium pullulans, Mucor sp and Fusarium sp. The range of fungal colonies on Sea Algae Kappaphycus alvarezii at the age of 25 days by the dilution factor, namely the 4000 colony 10-3, 10-4 and 10-5 of 80,000 colonies are 100,000 colonies, then at the age of 35 days with a 10-3 dilution factor of 1000 colonies , 10-4 ie 40,000 colonies and at the age of 45 days by the dilution factor yaitu7000 colony 10-3, 10-4 and 10-5 of 10,000 colonies are 500,000 colonies. Keywords: Sea Algae, Kappaphycus alvarezii, Fungi, tending age, colony.